Frank Maxwell Andrews papers - Andrews, Frank Maxwell, 1884-1943.
Correspondence, memoranda, speeches, reports, articles, military records, flight records, financial records, newspaper clippings, photographs, and other papers relating chiefly Andrews's service primarily in the U.S. Army Air Service (later the U.S. Army Air Corps). Subjects include the organization and administration of the air arm of the U.S. War Dept. and operations of the U.S. Army Caribbean Defense Command at the beginning of World War II. Correspondents include Henry Harley Arnold, Lawrence Dale Bell, Gerald C. Brant, George H. Brett, James Eugene Chaney, Malin Craig, Alexander P. de Seversky, Reuben Hollis Fleet, Benjamin Delahauf Foulois, Louis Arthur Johnson, George C. Kenney, Hugh Johnston Knerr, Frank Dorwin Lackland, Arthur Bliss Lane, Boaz Walton Long, Lesley James McNair, George C. Marshall, H.C. Pratt, Augustine Warner Robbins, Carl Spaatz, Henry L. Stimson, Ralph Talbot, Walter Reed Weaver, Oscar Westover, Harry Hines Woodring, and Burdette S. Wright.
Air Force officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arnold, Henry Harley, -- 1886-1950 -- Correspondence; Bell, Lawrence Dale, -- 1894-1956 -- Correspondence; Brant, Gerald C. -- Correspondence; Brett, George H. -- 1886-1963 -- Correspondence; Chaney, James Eugene, -- 1885-1967 -- Correspondence; Craig, Malin, -- 1875-1945 -- Correspondence; De Seversky, Alexander P. -- 1894-1974 -- Correspondence; Fleet, Reuben Hollis, -- 1887-1975 -- Correspondence; Foulois, Benjamin Delahauf, -- 1879-1967 -- Correspondence; Johnson, Louis Arthur, -- 1891-1966 -- Correspondence; Kenney, George C. -- 1889-1977 -- Correspondence; Knerr, Hugh Johnston, -- 1887-1971 -- Correspondence; Lackland, Frank Dorwin, -- 1884-1943 -- Correspondence; Lane, Arthur Bliss, -- 1894-1956 -- Correspondence; Long, Boaz Walton, -- 1876-1962 -- Correspondence; McNair, Lesley James, -- 1883-1944 -- Correspondence; Marshall, George C. -- 1880-1959 -- Correspondence; Pratt, H. C. -- 1882-1966 -- Correspondence; Robins, Augustine Warner -- Correspondence; Spaatz, Carl, -- 1891-1974 -- Correspondence; Stimson, Henry L. -- 1867-1950 -- Correspondence; Talbot, Ralph, -- 1897-1918 -- Correspondence; Weaver, Walter Reed, -- 1885-1944 -- Correspondence; Westover, Oscar, -- 1883-1938 -- Correspondence; Woodring, Harry Hines, -- 1887-1967 -- Correspondence; Wright, Burdette S. -- Correspondence; United States. -- Army -- History -- World War, 1939-1945.; United States. -- Army. -- Air Corps; United States. -- Army. -- Air Service; United States. -- Army. -- Caribbean Defense Command; United States. -- War Department; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Caribbean Area; Air Force officers